IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN PELAYANAN ADMINISTRASI - Anggita Wahyu Sonia (Program Studi Manajemen Pendidikan Islam, 2025)
A management information system is an information system that exists within an organization by carrying out functions to provide all information that affects all operations in an educational institution. The type of method used is library research, namely research in which the study uses library data in the form of books as a data source. To obtain optimal service quality in schools, much is determined by the ability to collaborate elements owned by schools that are mutually exclusive. related to showing that there is an integrated and complete service within the school. The systems used in schools vary according to the policies of the school or institution. There are many information systems used, one of which is Dapodik. The importance of information systems can simplify school services, especially in the administrative sector, and can also improve the quality of the school or institution. There are various types of information systems that can be used according to the needs of each school or institution